The utility of a real-time PCR to detect Leptospira in a routine diagnostic setting - Chanda, Raphael (Department of Pathology, 2023)
Leptospirosis is a neglected zoonotic infection with world-wide distribution. A paucity of leptospirosis data from the African continent exists, mainly due to limited access to diagnostics. The clinical presentation ranges from mild to severe disease with multi organ involvement, while the mild form mimics another common tropical disease i.e., malaria. The gold standard for diagnostic detection currently is an immunological test discerning the presence of specific antibodies present in the immune phase of the disease. The serological methods are hindered by the inability to distinguish past from current infection and utility limited to only the immune phase of the disease. Due to lack of sensitivity and specificity in serological methods, improved diagnostic methods are needed to aid early identification in the acute phase. Methods should also distinguish saprophyte and pathogenic species. To address this gap, we developed an inhouse PCR assay targeting the microbe's rrs and lipL32 genes, using primer sets previously reported in literature to be both sensitive and specific for pathogenic Leptospira spp. Using inhouse constructed plasmids, we did a non-clinical, technical validation employing probe-based, real time polymerase chain reaction assays and a locally available commercial kit. Although our assay needs further optimization, we demonstrated that the PCR reliably detected 100 copies and 1000 copies of Leptospira rrs and lipL32 targets respectively. To test specificity, we did real-time PCR with pure DNA from a selected set of pathogens known to be prevalent in bacteremia's in local settings and observed that the rrs target was amplified with Group B streptococci as template but no other tested pathogens, while no non-specific amplification for lipL32 was observed. The non-specific amplification had been reported previously in the literature, suggesting the rrs gene is not a good target to use, even when primers are specifically designed to only detect Leptospira rrs. Future work using the assay should include optimizing assay performance using DNA extracted from the ideal clinical samples to detect Leptospira, namely urine and blood of patients clinically suspected to have leptospirosis. However, the assay demonstrated potential for use as a diagnostic PCR using the constructed plasmid, but further optimization to improve PCR efficiency and assessing its performance in clinical setting is required